ความต่างในความเหมือนของพิธีกรรมบูชาพระธาตุสองฝั่งโขง The Unity in Diversity of the rite to relics worship of the two Banks of Mae Khong River - Weerayut Ledphonsatit วีรยุทธ เลิศพลสถิต (Journal of Fine and Applied Arts Khon Kaen University, 2016)
ความต่างในความเหมือนของพิธีกรรมบูชาพระธาตุสองฝั่งโขง มีวัตถุประสงค์ใน การศึกษา เพื่อศึกษาความแตกต่าง และความเหมือน ของพิธีกรรมบูชาพระธาตุ สองฝั่งโขง ในงานวิจัยนี้หมายถึงพระธาตุพนม และพระธาตุหลวง เป็นการศึกษาที่ใช้กระบวนการวิจัยเชิงคุณภาพ โดยมีประชากรและกลุ่มตัวอย่าง ในพื้นที่ อำเภอธาตุพนม จังหวัดนครพนม และแขวงนครหลวงเวียงจันทน์ เครื่องมือที่ใช้ในการวิจัย ประกอบด้วย แบบสำรวจ แบบสังเกต แบบสัมภาษณ์ และการสนทนากลุ่ม แล้วรวบรวมนำมาวิเคราะห์ด้วยทฤษฎีประวัติศาสตร์, ทฤษฎีการแพร่กระจายทางวัฒนธรรม และทฤษฎีโครงสร้างหน้าที่ นำเสนอโดยใช้วิธีพรรณนาวิเคราะห์ จากการศึกษาพบว่า นัยความต่างในความเหมือน ของพิธีกรรมบูชาพระธาตุสองฝั่งโขง ประเด็นแรก ความต่างในความเหมือน ของพิธีกรรมบูชาพระธาตุสองฝั่งโขงจากมุมมองของตำนานอุรังคธาตุ ดังนั้นจึงสรุปได้ว่า พิธีกรรมบูชาพระธาตุสองฝั่งโขง จากมุมมองของตำนานอุรังคธาตุมีความหมายและความสำคัญ คือ 1. พิธีกรรมบูชาพระธาตุสองฝั่งโขงในมิติความศักดิ์สิทธิ์และอิทธิฤทธิ์ปาฏิหาริย์ 2. พิธีกรรมบูชาพระธาตุสองฝั่งโขงในมิติเรื่องกรรม บาป – บุญ นรก – สวรรค์ 3. พิธีกรรมบูชาพระธาตุสองฝั่งโขงในมิติเรื่องพญานาคและบั้งไฟพญานาค 4. พิธีกรรมบูชาพระธาตุสองฝั่งโขงในมิติความเชื่อเรื่องผี และ5. พิธีกรรมบูชาพระธาตุสองฝั่งโขงในมิติของจารีตประเพณีฮีตสิบสองคองสิบสี่ ดังนั้น เมื่อมีพระอรหันต์ทั้ง 5 ได้ประดิษฐานพระบรมสารีริกธาตุขององค์พระสัมมาสัมพุทธเจ้า ที่พระธาตุพนมและพระธาตุหลวงแล้ว ก็มีการเฉลิมฉลองกัน โดยเทพเจ้าในห้วงจักรวาลมีพระอินทร์ได้ป่าวร้องกันลงมาถวายสักการบูชาพระธาตุพนมและพระธาตุหลวงเล่นมหรสพตลอดคืน นอกจากนี้ยังได้แต่งตั้งให้เทวดาทำหน้าที่ปกปักษ์รักษาข้าวของพญาทั้ง 5 ที่ตั้งไว้บูชาพระธาตุทั้ง 4 ด้านพร้อมด้วยบริวารอีก 4,000 องค์ และมเหศักดิ์หลักเมืองอีก 3 ตน ให้อยู่เฝ้าดูแลรักษาพระอุรังคธาตุ และสิ่งของบูชาพระธาตุพนม และพระธาตุหลวงต่อไป ประเด็นที่สอง ความต่างในความเหมือน ของพิธีกรรมบูชาพระธาตุสองฝั่งโขง จากมุมมองของปัจจุบัน มี 2 พิธีกรรม คือ พิธีกรรมบูชาพระธาตุประจำปี และพิธีกรรมบูชาพระธาตุประจำวัน ซึ่งพิธีกรรมบูชาพระธาตุประจำปี มี 3 ลำดับขั้น ประกอบด้วย ขั้นที่ 1.พิธีก่อนพิธีกรรมบูชาพระธาตุประจำปี ขั้นที่ 2. พิธีระหว่างพิธีกรรมบูชาพระธาตุประจำปี และขั้น 3. พิธีหลังพิธีกรรมบูชาพระธาตุประจำปี และ พิธีกรรมบูชาพระธาตุพนมประจำวัน มีพิธีที่สำคัญ 2 พิธี คือ พิธีบนบาน - พิธีแก้บนพระธาตุ และ พิธีเวียนเทียนบูชาพระธาตุ จะเห็นได้ว่าแม้จะเป็นการประกอบพิธีกรรมบูชาพระธาตุที่บรรจุพระบรมสารีริกธาตุขององค์พระสัมมาสัมพุทธเจ้าพระองค์เดียวกัน ด้วยแรงศรัทธาเช่นเดียวกัน แต่รูปแบบของการประกอบพิธีกรรมแตกต่างกันไปตามบริบทของพื้นที่ชุมชน The study of the different similarity of the rites to worship the stupa contained Buddha relics on both sides of the Mekong River aims to investigate the difference and similarity of these rites. In this study, the stupa contained Buddha relics cover Phra That Phanom and Phra That Luang. This study is a qualitative study with population and sample groups in the areas of That Phanom district in Nakhon Phanom province, Thailand and Vientiane, Laos. The tools used in data collection include surveys, observations, and structured interviews and focused group discussions. The collected data then was analyzed by using the History Theory, Cultural Diffusion Theory, and Structural-functional Theory. The results found are then presented in a descriptive analysis method. The results reveal that, firstly, the different similarity of the rites was perceived following the legend of Urankathat. It can be concluded that the rites to worship the Buddha relics stupa on both sides consist of both signification and significance. These include the dimension of holiness and supernatural myth, the dimension of karma and good deeds, heaven – hell, the dimensions of the Nagas and Naga fireballs, the dimensions of spiritual beliefs, and the dimension of Heet Sib Song Kong Sib See tradition. When the five Arahants (the liberated Buddhist monks) had located the Buddha relics at Phra That Phanom and Phra That Luang, the Buddhist followers then began to celebrate about it and around the stupa. The Indra who lived in the universe also came down to join the celebration and pay respect to Phra That Phanom and Phra That Luang. Furthermore, the Indra also appointed angels to protect properties of all 5 Nagas that were set up as offerings to the stupa on all four directions. Other four thousands angels and three city ruler spirits had been designated the serve as protecting the Buddha relics and contributes to both of the stupa as well. Secondly, the different similarity of the rites to worship the stupa based from the current perspectives consists of 2 kind of rituals, including the annual and daily worship rituals. The annual worship rituals consist of three steps:1) the pre-worship ritual, 2) between the worship ritual, and 3) the post worship ritual. The daily worship rituals include two kinds of rituals: the sacrifice and the candle light walk process. Thus, it can show that even though these rites were to worship the stupa that contained the relics of the same Buddha, they performed differently following the different area of the communities were.